До питання про етимологію праворозуміння - Дудаш, Т.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
Правопонимание – длительный процесс правоназывания в прошедшем, настоящем и будущем времени. Это заключение автор основывает на анализе этимологии правопонимания в разных языковых семьях мира, сравнительной характеристике термина «право» и производных от него терминах в славянских языках (романо-германская правовая семья), в англо-американской и дальневосточной(китайской) правовых семьях. The understanding of law (law-understanding) is viewed as a long-lasting process of law nomination in
past, present, and future. This conclusion is drawn from the presented analysis of the etymology of law-understanding in different language families, comparative characteristics of the term “law” and its derivatives
in Slavic languages (the continental law family), English, American and Oriental (Chinese) law families.